Coronary microvascular dysfunction is associated with cardiac time intervals in women with angina and no obstructive coronary artery disease: An iPOWER substudy. Issue 6 (22nd April 2019) - Pena, Adam; Michelsen, Marie Mide; Mygind, Naja Dam; Gustafsson, Ida; Høst, Nis; Bech, Jan; Kastrup, Jens; Hansen, Henrik Steen; Hansen, Peter Riis; Prescott, Eva
Abstract: Background: Coronary microvascular dysfunction (CMD) may cause angina in the absence of obstructive coronary artery disease (CAD) and increases the risk of future adverse cardiovascular events. Transthoracic Doppler echocardiography (TTDE) with pharmacological stress can assess coronary flow velocity reserve (CFVR), a measure of coronary microvascular function. However, simpler methods would be preferable for diagnosing CMD. Therefore, we examined the relationship between CFVR and cardiac time intervals measured by TTDE in a cohort of women with angina and no obstructive CAD. Methods: In a prospective cohort study, we included 389 women with angina, left ventricular ejection fraction > 45%, and no obstructive CAD. CMD was defined as CFVR < 2.0. The study population was divided into three groups according to cutoff values of CFVR < 2, 2 ≤ CFVR ≤ 2.5, and CFVR > 2.5. Isovolumic contraction time (IVCT), ejection time (ET), and isovolumic relaxation time (IVRT) were measured by tissue Doppler M‐mode, and the myocardial performance index (MPI = (IVCT + IVRT)/ET) was calculated. Results: Coronary microvascular dysfunction was associated with increasing age, hypertension, higher resting heart rate, and lower diastolic blood pressure. Moreover, CMD was associated with higher E/e′ ratio ( P  = 0.002) and longer IVCT ( P  < 0.001), higher MPI ( P  < 0.001) and shorter ET ( P  = 0.002), but not with IVRT or conventional measures of left ventricular geometry, mass, and function. In multivariable analysis, longer IVCT ( P  < 0.001) and higher MPI ( P  = 0.002) remained associated with CMD. Conclusion: In women with angina and no obstructive CAD, CMD is associated with longer IVCT and higher MPI indicating a link between CMD and subtle alternations of systolic and combined measures of cardiac time intervals.